'EIN LAND DER ANWESENDEN': DOROTHEE ELMIGER'S POLITICAL ENGAGEMENT WITH SWITZERLAND. (9th June 2016) - Robinson, Alan
ABSTRACT: The fiction of Dorothee Elmiger combines formal experimentation with political engagement. Her first novel, Einladung an die Waghalsigen (2010), depicts an isolated, stagnant territory which, as in the parables of Max Frisch or Friedrich Dürrenmatt, stands at an allegorical remove from Switzerland. By contrast, the formally starker and thematically bleaker Schlafgänger (2014) engages with disturbing conditions in actual places within or in relation to a Switzerland which is clearly inseparable from the rest of the world. Elmiger's representation of a transnationally connected, porous Switzerland can be interpreted as a response to the recent political swing to the right and to escalating controversies about migration, asylum seekers and foreign policy, and located within the literary discourse of 'critical patriotism'. In opposing the exclusionist insularity of the 'Schweizerische Volkspartei' (SVP), which remains rooted in the popular convictions and propaganda symbols of the Second World War, Elmiger envisages a pluralistic, inclusive country. This imagined community is evoked through an innovative form which has evolved from Elmiger's experimental text, 'Die Anwesenden': in polyphonic collaboration, her characters voice an emergent, collective consciousness that registers subtle shifts in sensibility and public discourses and explores complex issues of collective responsibility, complicity or guilt. Dorothee Elmigers Romane verbinden formale Experimentierfreude mit politischem Engagement. Ihr erster Roman, Einladung an die Waghalsigen (2010), erzählt von einem stillgelegten, erstarrten 'Gebiet', das wie in den Parabeln von Max Frisch und Friedrich Dürrenmatt in einer allegorischen Distanz zur Schweiz steht. Schlafgänger (2014) hingegen ist sowohl formal radikaler als auch thematisch düsterer und handelt von harten Gegebenheiten in realen Städten, die in einer global vernetzten Schweiz liegen oder Verbindungen zu ihr aufweisen. Elmigers Vorstellung von einer transnationalen, porösen Schweiz wird hier als Antwort auf den politischen Rechtsrutsch und die zunehmenden Kontroversen über Masseneinwanderung, Asylsuchende und Aussenpolitik der letzten Jahre gedeutet und in den literarischen Diskurs des 'kritischen Patriotismus' eingeordnet. Als Gegenbild zum abgrenzenden Isolationismus der 'Schweizerischen Volkspartei' (SVP), die im Reduit‐Denken und der Igelmentalität der 'geistigen Landesverteidigung' verhaftet bleibt, entwickelt Elmiger die Vision eines pluralistischen, inklusiven Landes. Diese imaginierte Gemeinschaft wird durch eine innovative Form evoziert, die aus Elmigers experimentellem Kurztext 'Die Anwesenden' herausgewachsen ist: Im Zusammenspiel ihrer sich abwechselnden Stimmen tragen die Figuren zum Entstehungsprozess eines kollektiven Bewusstseins bei, das in der Lage ist, subtile Verschiebungen im subjektiven Empfinden und in öffentlichen Diskursen zu registrieren und heikle Fragen von kollektiver Verantwortung, Komplizenschaft und Schuld auszuloten.